ANALISIS KESULITAN SISWA KELAS 4 DALAM MEMAHAMI KONSEP PECAHAN DAN IMPLIKASINYA TERHADAP PEMBELAJARAN MATEMATIKA - Nurul Aulia Rahma; Siti Amalia Aunilla; Kowiyah Kowiyah (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyze the difficulties of grade 4 students in understanding the concept of fractions and their impact on mathematics learning. The research participants consisted of 4th grade students at an elementary school in City Research finds that many students have difficulty understanding the concept of fractions, especially in dividing fractions, simplifying, and comparing fractions. Apart from that, it was also found that this difficulty was related to a lack of understanding of basic number concepts and poor basic mathematical operation skills. The results of this research indicate that there is a need to improve the structure and focus of learning so that students understand the concepts better. The use of more interactive learning media also needs to be considered to increase student understanding. The aim of this research is to help grade 4 students overcome difficulties in understanding the concept of fractions in mathematics learning. Through interactive learning, it is hoped that the mathematics learning process can be improved.